2004
DOI: 10.1007/s11167-005-0106-5
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and physicochemical treatment of flax fibers

Abstract: Conditions were found for separating concomitant substances from cellulose in short flax fibers by treatment with surfactant and enzyme solutions. The chemical composition of the treated fibers was analyzed, and their structural organization was studied by IR Fourier spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…Unfortunately, in recent decades the popularity of the flax plantations has decreased, not only in Poland, but all over the world [ 30 ]. This tendency could be explained by several reasons:…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, in recent decades the popularity of the flax plantations has decreased, not only in Poland, but all over the world [ 30 ]. This tendency could be explained by several reasons:…”
Section: Introductionmentioning
confidence: 99%
“…Also we suggest that the treatment of the cotton fiber and all the cellulosic fiber (cotton, linen) with α-amylase enzyme causes partial removal of concomitant substances (fats, pectins, and lignin) from cellulose. This finding is agreement with (Shamolina et al, 2004) that found the treatment On the other hand, results in Fig. 79 showed FTIR spectra of silk dyed with madder dye mordanted with alum after α-amylase treatment with different concentration for different durations (10U/ml at 1, 3 h).…”
Section: Ftir Spectra Of Fabrics Treated With α-Amylasesupporting
confidence: 91%
“…samples studied (i.e., the control and transgenic fibers) and very similar to that for purified cotton cellulose, 14 but the bands differ in terms of their absorption intensity. The band could be deconvoluted into four Lorenzian components (Figure 6) at 3460, 3410, 3350, and 3300/cm.…”
Section: Vibrational Datamentioning
confidence: 81%
“…However, they are also present in the primary wall of individual fibers, and therefore are constituents of the fibers themselves. 14 We determined the content of these compounds in transgenic flax fibers and compared them with the contents for the control fibers (Figure 2). The data showed no significant changes in the contents of cellulose, lignin, or pectin.…”
Section: The Chemical Analysis Of the Stem And Fiber Constituentsmentioning
confidence: 99%